Triptans Use for Migraine Headache among Nonelderly Adults with Cardiovascular Risk - Alwhaibi, Monira (Pain Res Treat, 2016)
Objective. To examine the association between the cardiovascular (CV) risk factors and triptans use among adults with migraine. Methods. A retrospective cross-sectional study design was used. Data were derived from 2009–2013 Medical Expenditure Panel Survey (MEPS). The study sample consisted of adults (age > 21 years) with migraine headache (N = 1,652). Multivariable logistic regression was used to examine the relationship between CV risk factors and triptans use. Results. Overall, 21% adults with migraine headache used triptans. Nearly two-thirds (61%) of adults with migraine had at least one CV risk factor. A significantly lower percentage of adults with CV risk (18.1%) used triptans compared to those without CV risk factors (25.5%). After controlling for demographic, socioeconomic status, access to care, and health status, adults with no CV risk factors were more likely to use triptans as compared to those with one CV risk factor (AOR = 1.83, 95% CI = 1.17–2.87). There were no statistically significant differences in triptans use between those with two or more CV risk factors and those with one CV risk factor. Conclusion. An overwhelming majority of adults with migraine had a contraindication to triptans based on their CV risk factors. The use of triptans among adults with migraine and multiple CV risk factors warrants further investigation.